II-Preparation and characterization Schiff base Derivatives with some transition metal complexes (Baghdad Science Journal, 2007)
This research consists of the synthesis of some Schiff bases as ligands, the following type of ligands: (2-hydroxy-benzylidene)- thiourea = (L1) (2-hydroxy-benzylidene)- urea = (L2) The complexation of these ligands with some transition metal ions (Zn+2, Cd+2, Hg+2) was prepared. The Schiff bases with their corresponding prepared transition metal complexes have been characterized on the bases of their (C.H.N) elemental analysis, IR, UV-VIS, atomic absorption, the molar conductivity measurement and melting point.The structural geometries of complexes were suggested in solid state.